2017
DOI: 10.1111/ajgw.12320
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and sensory profiling of Shiraz wines co-fermented with commercial non-Saccharomycesinocula

Abstract: Background and Aims The choice of yeast strain(s) to conduct the fermentation can greatly affect wine chemical and sensory profile. Even though the use of non‐Saccharomyces co‐inocula to build complexity and diversify styles is increasingly in vogue, a limited number of such products are available to date, and more research is required to guide their use in the wine industry. This study evaluates the potential of commercial yeast inocula to modulate the quality of Shiraz wines at two maturity levels. Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 60 publications
6
66
1
Order By: Relevance
“…A substantial decrease in ethanol production inevitably implies carbon rerouting toward the formation of other central metabolites to maintain both mass and redox balances during fermentation. Thus, higher production of glycerol, with an average increase of 50%, was found for M. pulcherrima under sequential inoculation compared with S. cerevisiae in pure culture, as previously reported (Comitini et al, 2011;Hranilovic et al, 2018). This observation can be explained first by the high capacity of M. pulcherrima to produce glycerol during the first part of the fermentation.…”
Section: Interactions Between M Pulcherrima and S Cerevisiae Changesupporting
confidence: 85%
See 1 more Smart Citation
“…A substantial decrease in ethanol production inevitably implies carbon rerouting toward the formation of other central metabolites to maintain both mass and redox balances during fermentation. Thus, higher production of glycerol, with an average increase of 50%, was found for M. pulcherrima under sequential inoculation compared with S. cerevisiae in pure culture, as previously reported (Comitini et al, 2011;Hranilovic et al, 2018). This observation can be explained first by the high capacity of M. pulcherrima to produce glycerol during the first part of the fermentation.…”
Section: Interactions Between M Pulcherrima and S Cerevisiae Changesupporting
confidence: 85%
“…This species has also been associated with a reduction in the final content of ethanol (Contreras et al, 2014;Quirós et al, 2014;Varela et al, 2016). Finally, combining M. pulcherrima with S. cerevisiae results in changes in the formation of aromas, with an increase in the final concentration of higher alcohols (Rodríguez et al, 2010;Sadoudi et al, 2012) and variations in the production of ethyl esters and acetate esters depending on the fermentation conditions (Rodríguez et al, 2010;Comitini et al, 2011;Varela et al, 2016;Hranilovic et al, 2018). Overall, wines fermented with M. pulcherrima are perceived as more floral, with smoky aromas (González-Royo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported higher total final anthocyanin concentrations in sequential fermentations involving L. thermotolerans than in the S. cerevisiae controls. The differences varied from 8% to 10% [34,89]. Additionally, the higher coloration of anthocyanins produced by lactic acid acidification at a low pH notably influences the final color intensity, which is higher than that of S. cerevisiae [6,18,35,36].…”
Section: Lachancea Thermotoleransmentioning
confidence: 97%
“…This has meant that winemakers delay the harvest date because of wineries operating at full capacity, thereby causing a part of the crop to overripe in the vineyard [70]. Hranilovic, et al [71] reported that the glycerol content of a Shiraz wine from early harvest grapes (approximately 265 g/L TSS) was much higher than those from the late harvest (approximately 325 g/L TSS), with a M. pulcherrima strain (followed by a S. cerevisiae inoculum), producing early and late harvest wines with 10.51 and 12.59 g/L glycerol, respectively. Juice with high sugar concentration also leads to an excess in acetic acid, which can be explained by yeasts trying to maintain redox balances by using surplus NAD(P) + accumulated during the synthesis of fermentation metabolites [62,[72][73][74].…”
Section: Glycerolmentioning
confidence: 99%